2011
DOI: 10.1136/bjsports-2011-090306
|View full text |Cite
|
Sign up to set email alerts
|

Conventional testing methods produce submaximal values of maximum oxygen consumption

Abstract: These findings go against the concept that a plateau in oxygen consumption measured during the classically described INC and VER represents a systemic limitation to oxygen use. The reasons for a higher VO(2) during INC(F) following the DEC test are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 83 publications
6
53
3
1
Order By: Relevance
“…For example, the Journal of Applied Physiology published specific contents about fatigue mechanisms during exercise (104; 2008), highlighting central mechanisms that could be involved in the exercise regulation. The BJSM published a series of articles which could support the CGM (46; 2012), including studies that challenged the traditional concept of VO 2MAX 26 27 or suggested a probable central regulation during exercise 28. Also, reviews, letters and rebuttals have added more focus on this topic 29–33…”
Section: Increased Acceptance Of a Centrally Regulated Effort Modelmentioning
confidence: 99%
“…For example, the Journal of Applied Physiology published specific contents about fatigue mechanisms during exercise (104; 2008), highlighting central mechanisms that could be involved in the exercise regulation. The BJSM published a series of articles which could support the CGM (46; 2012), including studies that challenged the traditional concept of VO 2MAX 26 27 or suggested a probable central regulation during exercise 28. Also, reviews, letters and rebuttals have added more focus on this topic 29–33…”
Section: Increased Acceptance Of a Centrally Regulated Effort Modelmentioning
confidence: 99%
“…Stewart and Sleivert (27) used a treadmill at 13km/h with 20% grade and a maximal VO 2max test that had an incremental increasing speed design. By using an incremental increasing speed design for establishing VO 2max , the maximal VO 2 is perhaps not the real VO 2max that Beltrami et al (4) found. In the present study, a non-motorized treadmill was used, which allows to adjust the velocity naturally during a running test.…”
Section: Stewart and Sleivertmentioning
confidence: 92%
“…They provide strong evidence that Hill over-interpreted the finding from his original relatively simple experiments. The studies of Mauger and Sculthorpe2 and Beltrami et al 3 should insure that no longer can Hill's classic experiments be used as absolute proof that a maximal cardiac output ‘limits’ maximal exercise performance as a result of a ‘poisonous’ lactic acidosis.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The issue begins with the complementary studies of Lex Mauger et al 2 from the University of Bedfordshire and Fernando Beltrami and his associates3 from the University of Cape Town. Their studies disprove perhaps the most fundamental idea on which Hill based his entire philosophy.…”
Section: When Is Vo2 Really ‘Max’?mentioning
confidence: 99%